PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE INDEX CARD MATCH TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 17 PADANG - Arafat, Yasser; Anggraini, Villia; Harisman, Yulyanti (STKIP PGRI Sumbar, 2014)
ABSTRACT This research was aimed at revealing whether the mathematics conceptual understanding of the students taught by using Index Card Match active learning strategy was better than that of students taught by using conventional learning. This was an experimental research which used random toward the subject design. The population of the research was all of students in class VIII of SMPN 17 Padang registered in Academic Year 2013/2014. The data of the research was analyzed by using t-test. The result of t-test indicated that the value of tcalculated was bigger than ttable on the level of significance Î±=0,05. Based on the result of data analysis, H0 was rejected signifying that the mathematics conceptual understanding of the students taught by using Index Card Match active learning strategy was better than that of students taught by using conventional learning in class VIII of SMPN 17 Padang.Â